Influence of Decadal Ocean Signals on Meteorological Conditions Associated With the Winter Haze Over Eastern China - Zhang, Wen; Dong, Xiao; Liu, Zhenxin; Lin, Renping; Luo, Hao (Frontiers in Environmental Science, 2021)
The possible influence of the Atlantic multidecadal oscillation (AMO) and the Pacific decadal oscillation (PDO) on the meteorological conditions associated with haze over central eastern China at decadal time scale was investigated using reanalysis and observational dataset for 1979−2018. Three indices, including Siberian high index (SHI), a normalized near-surface wind-speed index (WSI) and a potential air temperature gradient index (AGTI), are adopted to denote the weather conditions associated with haze. Results shown that the AMO and PDO are both highly correlated with the fluctuation of meteorological factors associated with haze on decadal scale. Although AMO and PDO were in opposite phases during the whole period, since 1997, they both changed phases (AMO shifted to a positive phase and PDO changed to negative) and become favorable for an anomalous dipole-type SLP pattern in the middle-high latitudes of East Asia. The AMO has played a leading role in decadal variation of the large-scale circulation system, while the PDO has had a closer relationship with the lower ventilation condition in eastern East Asia. On the decadal time scale, the AMO stimulates a zonal teleconnection wave train (the AMO northern Hemisphere pattern, ANH) that originates from the North Atlantic Ocean and passes through central Europe, the northern Ural Mountains, Lake Balkhash-Baikal, and central eastern China. During the positive phase of AMO, the ANH induces a stronger and westward shifted SH, with the central eastern China controlled by the anomalous high pressure. In addition, affected by the cyclone (anticyclone) anomaly over Hetao region and North China (the Sea of Japan), southerly wind anomalies dominate over central eastern China. Compared with the AMO, the wave train generated by the negative (positive) PDO phase mainly propagates in the Pacific region, and there is a strong anticyclonic (cyclonic) anomaly over the Northeast Pacific, guiding the air flow southward (northward) along the East Asian coast and thus suppressing (encouraging) the dispersion of pollutants and resulting in above (below)-normal haze episodes.